Optimizing Digital Wellness to Prevent Gadget Addiction and Brainrot in Youth of Lumbok Seminung, West Lampung - Puspandari Setyowati Sugiyanto; Andi Windah; Ida Nurhaida; Anna Gustina Zainal; Ahmad Riza Faizal (International Journal of Community Service Implementation, 2025)
The increasing use of gadgets among adolescents, particularly youth in Lumbok Seminung Sub-district, has led to negative impacts on mental health, with gadget addiction and brainrot as prominent examples. In Lumbok Seminung Sub-district, West Lampung, this phenomenon is becoming more widespread, threatening the quality of learning and psychological development of adolescents. This community service aims to optimize digital wellness to prevent gadget addiction and brainrot among youth. The activities were conducted by providing materials on mental health, digital wellness, and screen time management. Prior to the counseling sessions, pre-tests and post-tests were administered through written questions to the youth in Lumbok Seminung Sub-district, West Lampung. The results showed that, quantitatively, the youth’s knowledge of digital health was already at a fairly good baseline, with 70.8% of pre-test answers correctly addressing the importance of healthy gadget use. After the delivery of materials by the community service team, the youth’s understanding increased to 81.1%. This improvement was based on the pre-test and post-test results. Therefore, it can be concluded that this community service activity successfully had a positive impact, enhancing the youth’s understanding and awareness of the importance of using digital technology in a healthy and balanced manner. Through educational and participatory approaches, participants were equipped with knowledge about the concept of digital wellness, the potential dangers of gadget addiction, and concrete strategies for managing gadget use wisely.